2017
DOI: 10.1021/acs.jafc.7b01465
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dietary Supplementation with Selenium-Enriched Yeast Improves Cognitive Impairment, Reverses Synaptic Deficits, and Mitigates Tau Pathology in a Triple Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by multiple histopathological changes in the brain and by impairments in memory and cognitive function. Currently, there is no effective treatment that can halt or reverse the progression of this disease. Here, we explored the effects of 3 months of treatment with selenium-enriched yeast (Se-yeast), which is commonly used as a source of organic selenium (Se) for nutrition, on cognitive dysfunction and neuropathology in the tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 61 publications
(125 reference statements)
2
19
0
Order By: Relevance
“…Tau is the main protein associated with the stability of neuronal microtubules along with the MAPs (MAP1 and MAP2) (166). Long-term dietary supplementation (3 months) with Seenriched yeast (Se-yeast) in triple transgenic mouse model of Alzheimer disease (AD), significantly improved spatial learning, retention of neuronal memory and activity (167).…”
Section: Selenium Microbiota and Neurological Diseasesmentioning
confidence: 99%
“…Tau is the main protein associated with the stability of neuronal microtubules along with the MAPs (MAP1 and MAP2) (166). Long-term dietary supplementation (3 months) with Seenriched yeast (Se-yeast) in triple transgenic mouse model of Alzheimer disease (AD), significantly improved spatial learning, retention of neuronal memory and activity (167).…”
Section: Selenium Microbiota and Neurological Diseasesmentioning
confidence: 99%
“…Consistently with this data, there is also experimental evidence of positive outcomes in 3x-Tg mice that were given selenium-enriched yeast for 3 months. Interestingly, spatial memory was improved concomitantly with reduced neuroinflammation, GSK3β-dependent Tau phosphorylation and increased expression of synaptic proteins in the cortex and hippocampus (Zhang et al, 2017). In the same line, in a pilot study and a larger RCT (Kobayashi et al, 2019a,b), analyzed the impact of a 6-or 3-month probiotic supplementation with Bifidobacterium breve A1 in aged patients with MCI, respectively.…”
Section: Microbiota Modulationmentioning
confidence: 99%
“…Organic Se has attracted attention due to its advantages, including its enhanced biological activity, decreased toxicity, and diminished environmental pollution concern compared to inorganic Se. Many organic Se compounds have been shown to have therapeutic effects in AD mice models (Xie et al, 2017(Xie et al, , 2018Zhang et al, 2017aZhang et al, , 2018. Through a series of studies, Zhang et al showed that selenomethionine enhanced the antioxidant capacity, mitigated Aβ and tau pathology, reversed synaptic deficits, and ameliorated cognitive decline in AD mice (Song et al, 2014;Zhang et al, 2016Zhang et al, , 2017aZhang et al, , 2018, demonstrating the multitarget effect of Se in AD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Many organic Se compounds have been shown to have therapeutic effects in AD mice models (Xie et al, 2017(Xie et al, , 2018Zhang et al, 2017aZhang et al, , 2018. Through a series of studies, Zhang et al showed that selenomethionine enhanced the antioxidant capacity, mitigated Aβ and tau pathology, reversed synaptic deficits, and ameliorated cognitive decline in AD mice (Song et al, 2014;Zhang et al, 2016Zhang et al, , 2017aZhang et al, , 2018, demonstrating the multitarget effect of Se in AD treatment. Furthermore, impaired autophagy (Zhang et al, 2017b,c;Song et al, 2018) and mitochondrial dysfunction (Balaban et al, 2017) have been shown to be the targets of Se compounds in AD.…”
Section: Introductionmentioning
confidence: 99%